2022
DOI: 10.3389/fpsyt.2022.996406
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in rat prefrontal cortex kynurenic acid levels are involved in the enduring cognitive dysfunctions induced by tetrahydrocannabinol exposure during the adolescence

Abstract: IntroductionCannabis abuse during adolescence is a risk factor for cognitive impairments in psychiatric disorders later in life. To date, the possible causal relationship between cannabinoids, kynurenic acid (KYNA; i.e., a neuroactive metabolite of tryptophan degradation) and cognition has not been investigated in adolescence. Early exposure to delta 9-tetrahydrocannabinol (THC; i.e., the main psychotropic component of cannabis) causes enduring cognitive deficits, which critically involve impaired glutamatergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…It was also demonstrated that exposure to THC in adolescent rats (35-45 days) can cause deficits in short-term memory in adult animals tested in the Y-maze [74]. Interestingly, in this study, exposure of juvenile rats to THC induced a malfunction of the kynurenine pathway in the adult brain, specifically increasing the level of kynurenic acid in the medial prefrontal cortex.…”
Section: Alterations In Cognitive Functions Upon Direct Action On Cb ...supporting
confidence: 51%
See 1 more Smart Citation
“…It was also demonstrated that exposure to THC in adolescent rats (35-45 days) can cause deficits in short-term memory in adult animals tested in the Y-maze [74]. Interestingly, in this study, exposure of juvenile rats to THC induced a malfunction of the kynurenine pathway in the adult brain, specifically increasing the level of kynurenic acid in the medial prefrontal cortex.…”
Section: Alterations In Cognitive Functions Upon Direct Action On Cb ...supporting
confidence: 51%
“…Interestingly, the effects of cannabinoids on cognitive performance in animals change with age, with stronger negative effects being observed in the pubertal phase compared to the adult [72][73][74]. In view of this, Verrico and colleagues carried out a research of the effect of THC on working spatial memory and object recognition memory in adolescent monkeys.…”
Section: Alterations In Cognitive Functions Upon Direct Action On Cb ...mentioning
confidence: 99%
“…Mice were euthanized under deep anesthesia by pentobarbital (60 mg/kg, i.p.) (Amiri et al, 2017), brains were rapidly removed, the PFC dissected out from one brain's hemisphere on the ice-cold surface and directly placed into liquid nitrogen and then stored at À80 C for molecular evaluations (Beggiato et al, 2022). Another hemisphere was immersed in 10% formalin for evaluation of histological changes in the pyramidal area of the hippocampus (Anjomshoa et al, 2020).…”
Section: Molecular and Histopathological Evaluationsmentioning
confidence: 99%
“…Notably, increased levels of cerebral kynurenic acid have been detected in the aged brain and in several major neurological and psychiatric diseases [ 85 ]. Kynurenic acid has been also suggested to be related to cognitive impairments [ 86 ], which have been frequently discussed as possible markers of perioperative neurocognitive disorders [ 87 ]. A lower level of kynurenic acid has been associated with worse cognitive functioning in a bipolar depression group [ 88 ] ( Figure 2 ).…”
Section: Kynurenine Metabolites Involved In Brain Memory System and I...mentioning
confidence: 99%